Does Transcranial Magnetic Stimulation (TMS) primarily target premotor or motor cortex in precentral gyrus?. Issue 1 (January 2019) - Dubbioso, R.; Sørensen, P.J.; Thielscher, A.; Siebner, H.R.
Abstract : TMS can be used to map the corticomotor representations of hand muscles (HMs) in the precentral gyrus (PG), whose spatial peak is often not located in the primary motor hand area (M1HAND ) but shifts towards the caudal part of dorsal premotor cortex (PMd). We used magnetic resonance imaging (MRI) to test the hypothesis that "hand-knob" of PG shows different structural properties in individuals with a "premotor" representation compared to individuals with a "primary-motor" representation of HMs. Twenty-four volunteers underwent MRI and sulcus-shape-based TMS-mapping of right PG. T1-weighted-MRIs were used for neuronavigation and to calculate cortical-thickness of the PG. We also performed quantitative multiparameter mapping of the longitudinal relaxation rate as an index of cortical myelination and simulated the electric field strength induced by TMS in the hand-knob-region. In 14 out-of 24 individuals (58%), TMS mapping disclosed a spatial peak in the PMd ("PMd-subjects"), whereas the remaining 10 subjects (42%) showed maximal motor response in M1HAND ("M1HAND -subjects"). "M1-subjects" displayed a higher electric field strength in the rostral part of the M1HAND (p = 0.01). "PMd-subjects" showed an increase of regional-myelination in the PG (p = 0.033). The results support the notion of two distinct functional-microstructural phenotypes of corticomotor hand representations in human PG.